159. Genomic Epidemiology of MRSA at Intake to a Large Inner-City Jail: Evidence for Community Transmission Networks?. (26th November 2018) - Popovich, Kyle J; Snitkin, Evan S; Green, Stefan J; Aroutcheva, Alla; Schoeny, Michael; Payne, Darjai; Thiede, Stephanie; Zawitz, Chad; Hota, Bala; Hayden, Mary K; Weinstein, Robert A
Abstract: Background: USA300 is endemic in the community, with congregate settings potentially facilitating spread. The impact of community MRSA transmission networks on importation of MRSA into urban jails is unknown. We examined MRSA colonization isolates entering the jail and determined whether there are community transmission networks for MRSA that precede incarceration. Methods: HIV-infected and HIV-negative males incarcerated at the Cook County Jail were enrolled within 72 hours of intake. Surveillance cultures (nares, throat, and groin) were collected to determine prevalence of MRSA colonization. A survey was administered to identify predictors of colonization. Whole-genome sequencing (WGS) and phylogenetic analysis were integrated with epidemiologic data to identify community transmission networks. Results: A total of 800 males were enrolled (83% AA and 9% Hispanic); 58% were HIV-infected. The prevalence of MRSA colonization at intake was 19%. In multivariate analysis, methamphetamine use (METH), unstable housing, and prior jail incarceration were significant predictors of MRSA. Among HIV patients, injection drug use and HIV care at outpatient Clinic A that emphasize comprehensive care to the LGBTQ community were significant predictors of MRSA. Of the 31 (45%) patients with care at Clinic A, 14 had MRSA colonization. We sequenced 145 isolates from unique individuals, with 102 and 13 closely related to USA300 and USA500 reference genomes, respectively. USA300 strains from intake were diverse (median pairwise SNV distance = 109), with several small clusters noted. WGS revealed the high prevalence of MRSA in Clinic A was not due to clonal spread but rather an intermingling of distinct community transmission networks (strains were highly diverse; median pairwise SNV distance = 410). We did identify a 13-member community transmission network underlying spread of USA500 (figure). Members of this network were more likely to be HIV-infected ( P < 0.004), MSM ( P < 0.001), and METH ( P < 0.001). Conclusion: A high proportion of individuals enter jail already colonized with MRSA and colonization risk factors provide clues to community reservoirs for MRSA. WGS extended epidemiologic analysis and revealed community transmission networks that could be a potential focus for an intervention. Disclosures: All authors: No reported disclosures.